Odpowiedzi

2009-12-11T19:51:06+01:00
√4x²+4x+1=3
4x√4x+1=3
4x+2x√1=3
6x√1=3/:x
x√1=6:3
x√1=2
1 1 1
  • Użytkownik Zadane
2009-12-11T19:50:28+01:00
√4x²+4x+1=3
√(2x+1)²=3 pierwaistek z potegą sie redukuje i mamy
2x+1=3
2x=3-1
2x=2 /2
x=1
2009-12-11T19:56:07+01:00
√4x²+4x+1=3 wszystko jest pod pierwiastkiem oprócz =3

Δ=b²-4ac
Δ=(4)²-4*4*1
Δ=16-16= 0
√Δ= 0
x₁= -b-√Δ/2a x₂= -b+√Δ/2a
x₁= -4-0/2*8 -2 x₂= -4+0/2*8
x₁= -4/16 = -1/4 x₂= -4/16= -1/4

√4x²+4x+1=3 => √(x+1/4)²=3 [pierwiastek i potęga się redukują]
x+1/4 = 3
x=2¾